2007
DOI: 10.1093/hmg/ddm286
|View full text |Cite
|
Sign up to set email alerts
|

Brain-specific tryptophan hydroxylase 2 (TPH2): a functional Pro206Ser substitution and variation in the 5'-region are associated with bipolar affective disorder

Abstract: The neurotransmitter serotonin [5-hydroxytryptamine (5-HT)] controls a broad range of biological functions that are disturbed in affective disorder. In the brain, 5-HT production is controlled by tryptophan hydroxylase 2 (TPH2). In order to assess the possible contribution of TPH2 genetic variability to the aetiology of bipolar affective disorder (BPAD), we systematically investigated common and rare genetic variation in the TPH2 gene through a sequential sequencing and SNP-based genotyping approach. Our study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
94
2
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(98 citation statements)
references
References 33 publications
1
94
2
1
Order By: Relevance
“…Furthermore, several naturally occurring functional polymorphisms in the Tph2 gene have also been identified in mice (15), rhesus monkeys (42), chimpanzees (43), and humans (17)(18)(19). The existence of multiple rare variants in a single gene leading to the development of human pathologies is not a rare occurrence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, several naturally occurring functional polymorphisms in the Tph2 gene have also been identified in mice (15), rhesus monkeys (42), chimpanzees (43), and humans (17)(18)(19). The existence of multiple rare variants in a single gene leading to the development of human pathologies is not a rare occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…This enzyme catalyzes the conversion of the amino acid tryptophan to 5-hydroxytryptophan (5-HTP) that is subsequently decarboxylated to 5-HT by L-aromatic amino acid decarboxylase. Recent investigations of naturally occurring genetic polymorphisms in humans and mice have identified functional mutations in Tph2 that lead to pronounced reduction in enzyme activity (15,(17)(18)(19). A rare R441H TPH2 variant has been identified in individuals from a small cohort of elderly patients with major unipolar depression.…”
mentioning
confidence: 99%
“…Recently, it was found that the pure enzyme had intact kinetic properties, but decreased thermal stability and an increased rate of aggregation in vitro, supporting a role of this mutation in the clinical phenotype [Winge et al, 2007]. More recently, another rare missense mutation (p.P206S) has been reported to be associated with unipolar and bipolar depression in different populations [Cichon et al, 2008;Zhou et al, 2005b]. Molecular characterization of this mutation revealed that the enzyme behaved similar to the wild type, but had a moderately reduced thermal stability and increased rate of aggregation in vitro [Cichon et al, 2008].…”
Section: Mutations Within Thetph1 Andtph2 Genesmentioning
confidence: 97%
“…More recently, another rare missense mutation (p.P206S) has been reported to be associated with unipolar and bipolar depression in different populations [Cichon et al, 2008;Zhou et al, 2005b]. Molecular characterization of this mutation revealed that the enzyme behaved similar to the wild type, but had a moderately reduced thermal stability and increased rate of aggregation in vitro [Cichon et al, 2008]. The other coding nonsynonymous SNPs and synonymous SNPs in TPH2 have so far not been associated with any particular phenotype (see Supplementary Table S3 and Fig.…”
Section: Mutations Within Thetph1 Andtph2 Genesmentioning
confidence: 99%
See 1 more Smart Citation